Inspired Nitric Oxide and Modulation of Oxidative Stress During Cardiac Surgery - Elahi, Maqsood M.; Worner, Murray; Khan, Jawad S.; Matata, Bashir M. (Current Drug Safety, 2009)
Evidence in the literature is contradictory regarding the precise role of nitric oxide (NO) in modulating systemic inflammatory response induced by cardiopulmonary bypass (CPB). We studied the impact of inspired NO gas on physiological function and markers of inflammation-oxidative stress for subjects (n = 15, age 62+4.5 and 12/3 M/F) scheduled for coronary artery bypass graft (CABG) operation. Outcomes from subjects that received 5 ppm and 20 ppm of inspired NO (n = 5/group) were compared to those not given NO gas. Breath-to-breath measurement commenced at the start of intubation and continued up to 4h later. Indices of cardiovascular function, alveolar-capillary gas exchange and haematological parameters were not significantly different in outcomes for the inspired NO groups as compared with control. We observed a reduction in mean systemic arterial in all subjects at 30 min and 4h after bypass when compared with pre bypass values. Markers of systemic inflammatory response and oxidative stress increased during CPB particularly at 4h and 24h after the initiation of bypass. In contrast, we observed a reduction in expired NO, at 24h after surgery in the groups given inspired NO. In addition, there was also a significant reduction in oxidative stress markers in blood at 24h after surgery for the groups given inspired NO as compared with the control group. In contrast, cytokines response remained similar in all the three groups at all time points. The results suggested that inspired NO gas has an antioxidant property that reduces the levels of cell death, and is not associated with significantly worse-off physiological outcomes.
Keywords: Expired nitric oxide